Intra-Articular Dislocation of the Patella. (26th February 2013) - McHugh, Gavin; Ryan, Ed; Cleary, May; Kenny, Paddy; O'Flanagan, Shea; Keogh, Peter
Abstract : We present an unusual case of a chronic, irreducible intra-articular dislocation of the patella in an elderly nursing home resident. The patient had been unable to weight bear for 3 weeks. Radiographs in the emergency department (ED) confirmed the intra-articular dislocation with the superior pole lodged in the intercondylar notch. She underwent two failed closed reduction attempts and subsequently required an open reduction under general anaesthesia.